Edge Functionalization of Graphene and Two-Dimensional Covalent Organic Polymers for Energy Conversion and Storage - Xiang, Zhonghua; Dai, Quanbin; Chen, Jian-Feng; Dai, Liming (Advanced materials (Weinheim), 2016)
Edge functionalization by selectively attaching chemical moieties at the edge of graphene sheets with minimal damage of the carbon basal plane can impart solubility, film‐forming capability, and electrocatalytic activity, while largely retaining the physicochemical properties of the pristine graphene. The resultant edge‐functionalized graphene materials (EFGs) are attractive for various potential applications. Here, a focused, concise review on the synthesis of EFGs is presented, along with their 2D covalent organic polymer (2D COP) analogues, as energy materials. The versatility of edge‐functionalization is revealed for producing tailor‐made graphene and COP materials for efficient energy conversion and storage. The development of edge‐functionalized graphene (EFG) and 2D covalent organic polymers (2D COPs) is highlighted as multifunctional energy materials for efficient energy conversion in fuel cells and solar cells, as well as energy storage in batteries.